A conceptual polarimetry applied in X-ray polarization in the energy range of 10–30 keV. (1st September 2022) - Jiang, J.; Jiang, W.; Xu, Y.; He, H.; Liu, X.; Du, Y.; Sun, L.; Dong, Z.; Liu, X.; Yang, S.; Jiao, Y.; Dai, B.
Abstract: The lower energy part of the hard X-ray band, 10–30 keV, still remains unexplored for X-ray polarimetry. A photo-electric polarimetry based on a CMOS imaging sensor typed GMAX0505 was proven to be a candidate polarimeter applied in this energy band, the pixel size is 2.5 μm and X-ray detection depth is around 5 μm. Due to a limitation of its pixel shape, the sensors can not give the polarization angle of incoming X-rays directly, but predict the angle by utilizing the asymmetric response at different polarization angle of X-rays. In this study, we construct a simplified sensor based on the structure of the GMAX0505, utilizing the GEANT4 toolkit. The variation trend of modulation factor in the simulation is similar with those measured in the reference at 12.4-keV and 24.8-keV X-rays. Based on the simulation framework, we change the pixel shape from square to hexagon with the same pixel pitch of 2.5 μm and define three directions along the symmetry axis of a pixel. Comparing the modulation curves obtained by solving the modulation curve function with three parameters, the modulation factor is around 10% and 23% at 12.4 keV and 24.8 keV in response to X-rays with different polarization angle and 100% linear polarization, the difference between predicted and incident polarization angle is less than 2.5° which is an estimate of the systematic error. Meanwhile, the degree of modulation is less than 1% in response to unpolarized X-rays. This study shows that similar sensors with a hexagonal pixel shape can give the modulation curve and directly predict the polarization angle of an X-ray source. It also provides a conceptual design for next photo-electric X-ray polarimetry in the energy band. In addition, the performance characterized by quality factor (QF) was compared for the sensors with different pixel pitch and the same pixel gap, the results show the QF is sensitive to a pixel pitch with different value and the value of the QF is maximum as a pixel pitch of the sensors is 0.75 μm under the same condition of pixel gap of 0.2 μm.